PELAKSANAAN PEMBELAJARAN AQIDAH AKHLAQ DALAM MATERI ADAB UNTUK PEMBENTUKAN KARAKTER AKHLAQUL KARIMAH SISWA KEPADA GURU - Wening Cahyaningtyas; Syamsuddin Syamsuddin; Indah Nurhidayati (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2023)
WENING CAHYANINGTYAS, Thesis, Implementation of Aqidah akhlaq Learning in adab material for the formation of character akhlaqul karimah students to teachers in class IX madrasah qur'aniyyah Al husnayain Surakarta Academic Year 2022/2023 This study aims to find out: 1) the implementation of Aqidah akhlaq learning for the formation of students' akhlaqul karimah character to teachers in class IX MQ Al Husnayain Surakarta. 2) Obstacles in the implementation of aqidah akhlaq learning in adab material for the formation of students' akhlaqul karimah character to teachers in class IX MQ Al Husnayain Surakarta 3). solution when there are obstacles in the implementation of aqidah akhlaq learning in adab material for the formation of character akhlaqul karimah students to teachers in class IX MQ Al Husnayain Surakarta. The study was conducted at Madarsah Qur'aniyyah Al Husnayain Surakarta from May to June. The research subjects were all residents of Madarsah Qur'aniyyah Al Husnayain Surakarta school and informants of principals, aqidah akhlaq teachers and students of Madrasah Qur'aniyyah Al Husnayain Surakarta. This research uses a qualitative approach with observation, interview and documentation methods. This data collection researchers use data analysis techniques, where in this analysis model there are three components, namely data reduction, data presentation and conclusions, which are carried out simultaneously in the data collection process, while to test the validity of triangulation. The results of this study: 1) The implementation of learning Aqidah akhlaq on Monday which was carried out after the congregational dhuhur prayer which was carried out in the madrasah hall which was attended by all grade IX students of madarasah qur'aniyyah al husnayain Surakarta with learning Aqidah akhlaq students are expected to increase faith and piety to Allah and have akhlaqul karimah students to the teacher. Adab siswa to guru is an effort to realize a civilized generation and berkhlaqul karimah so that it can set an example for others, 2) Obstacles in the implementation of learning Aqidah akhlaq there are several factors including teachers who are less clear in delivery, students who do not pay attention to monotan learning and learning that makes boredom, from these obstacles are expected to be a reference in learning evaluation, 3) The solution of some of these obstacles imposes everything only to Allah, always provides motivation and encouragement in doing good civilly, and provide a good example so that students can emulate because the best role model in school is a teacher.